Interpretable Machine Learning Approach for Identifying the Tip Sharpness in Atomic Force Microscopy. (December 2022) - Zaki, Mohd; Kasimuthumaniyan, S.; Sahoo, Sourav; Jayadeva,; Gosvami, Nitya Nand; Krishnan, N. M. Anoop
Abstract: Atomic force microscopy (AFM) is routinely used with indentation techniques to characterize the plastic deformation of materials. The accurate quantification of the features associated with the indent, which is used to quantify the hardness and indentation deformation mechanisms, depends on the sharpness of the AFM tip used for imaging. However, identifying the tip-sharpness of an atomic force microscope requires non-trivial measurements. Here, using machine learning, we develop a model to predict the tip sharpness of the AFM cantilever directly from the indent images. Further, we employ explainable machine learning models, such as integrated gradients and gradient shap, to interpret the features learned by the model. Altogether, we show that machine learning approaches can accelerate experiments by providing non-trivial information about the instrument performance, thereby enabling researchers to perform better quality experiments. Graphical abstract: Image, graphical abstract